An Ultrasonic Microrobot Enabling Ultrafast Bidirectional Navigation in Confined Tubular Environments - Cui, Meng; Zhen, Liyun; Bai, Xingyu; Yu, Lihan; Chen, Xuhao; Liu, Jingquan; Liu, Qingkun; Yang, Bin (Nano-Micro Letters, 2025)
Pipelines are extensively used in environments such as nuclear power plants, chemical factories, and medical devices to transport gases and liquids. These tubular environments often feature complex geometries, confined spaces, and millimeter-scale height restrictions, presenting significant challenges to conventional inspection methods. Here, we present an ultrasonic microrobot (weight, 80 mg; dimensions, 24 mm × 7 mm; thickness, 210 μm) to realize agile and bidirectional navigation in narrow pipelines. The ultrathin structural design of the robot is achieved through a high-performance piezoelectric composite film microstructure based on MEMS technology. The robot exhibits various vibration modes when driven by ultrasonic frequency signals, its motion speed reaches 81 cm s−1 at 54.8 kHz, exceeding that of the fastest piezoelectric microrobots, and its forward and backward motion direction is controllable through frequency modulation, while the minimum driving voltage for initial movement can be as low as 3 VP-P. Additionally, the robot can effortlessly climb slopes up to 24.25° and carry loads more than 36 times its weight. The robot is capable of agile navigation through curved L-shaped pipes, pipes made of various materials (acrylic, stainless steel, and polyvinyl chloride), and even over water. To further demonstrate its inspection capabilities, a micro-endoscope camera is integrated into the robot, enabling real-time image capture inside glass pipes. Highlights: 1 An ultrasonic microrobot achieves bidirectional high-speed locomotion (81 cm s−1) in micro-pipes via frequency modulation. 2 MEMS-fabricated ultrathin piezoelectric composite film enables rapid navigation within confined pipeline (4 mm height), slope climbing (24.25°), and notable load-carrying (>36 times its weight). 3 The microrobot demonstrates agile locomotion across curved pipes, pipes made of various materials, and even over water; integrated micro-endoscope camera enables real-time imaging, highlighting great potential for efficient pipeline inspection.